KEABSAHAN AKTA PENDIRIAN PERSEROAN TERBATAS DENGAN SAHAM HARTA BERSAMA SUAMI ISTRI DITINJAU DARI ASAS ACTA PUBLICA PROBANT SESE IPSA - Kayla Raissafitri (Fakultas Hukum Universitas Udayana, 2023)
The study aims to evaluate the legality of the Limited Liability Company's establishment deed, which was created using the combined assets of a spouse, and the legal ramifications of any legal action taken following of cancellation of the Limited Liability Company's Establishment Deed. Data was gathered through a literature review of primary and secondary sources, utilizing a statutory approach and juridical-normative procedures as the research method. A Limited Liability Company Establishment Deed with a spouse's combined assets does not appear legitimate under the acta publica probant sese ipsa principle. A married couple is regarded as one entity under the regulation of the Civil Code along with the Marriage Law, there's no element of a legal consensus between them. However, in accordance with this principle, the Limited Liability Company's Establishment Deed will continue to be acknowledged as a true and legitimate legal document, at least until a third party brings a lawsuit and successfully argues in court that the deed is void. Because the company is still a legal entity when the agreement to take legal action is carried out, the legal activities that the company completed before the deed of the organization was revoked are still recognized as lawful.